PEMBERDAYAAN MASYARAKAT MELALUI PENANAMAN TOGA BUAH LEMON UPAYA PENCEGAHAN DAN PENANGGULANGAN COVID-19 - Dadang Sahroni; Neng Rani Permana; Latifatul Hasanah (Pastabiq : Jurnal Pengabdian Kepada Masyarakat, 2022)
The problem faced by the people of Palasarigirang Village is that the level of public health has decreased and the community's economy has decreased drastically. In public health services, there is a shortage of vitamin C which is usually sold in stalls and drug stores in Palasarigirang Village and its surroundings. In addition to this, the economic aspect of the Palasarigirang Village community has decreased which has an impact on the purchasing power of the community to be very low. The purpose of this community service is to increase community knowledge and skills on health through Family Medicinal Plants (TOGA) by planting lemon trees as an effort to overcome the scarcity of vitamin C herbally and to increase family economic resilience. The methods used are lectures and demonstration methods. The lecture method was carried out on the delivery of program socialization and material on land use and knowledge of the uses and benefits of lemons. While the demonstration method is used to provide examples of planting lemon trees and the actual implementation. As for the results of this community service, the people of Palasarigirang Village have knowledge and skills about planting lemon trees as well as their uses and benefits reaching 83.33% and in its implementation as many as 30 families of Palasarigirang Village residents, their home yards and village streets have lemon tree